(untitled) (Research, Society and Development, 2023)
Introduction: Mandibular osteoma is a benign lesion that can cause facial asymmetry and compromise the patient’s functionality. In these situations, surgical treatment is indicated. Virtual planning has been used by Oral and Maxillofacial Surgery and Traumatology, offering the possibility of detailed simulation of the intervention and creation of biomodels and surgical guides. Objective and case report: The article aims to explore the possibilities, benefits, challenges and limitations of virtual planning with free software for the surgical treatment of a patient with an osteoma in the mandibular body region. Surgical treatment for excision of the lesion was carried out in a hospital environment, under general anesthesia. Final considerations: The use of free software represents a viable alternative, especially in environments with limited financial resources, such as in the Unified Health System. These tools allow surgeons to create detailed three-dimensional models, biomodels and personalized surgical guides, improving precision and efficiency of procedures.